The Downregulation of Somatic A-Type K + Channels Requires the Activation of Synaptic NMDA Receptors in Young Hippocampal Neurons of Rats - Kang, Moon-Seok; Yang, Yoon-Sil; Kim, Seon-Hee; Park, Joo-Min; Eun, Su-Yong; Jung, Sung-Cherl (The Korean journal of physiology & pharmacology, 2014)
The downregulation of A-type K(+) channels (IA channels) accompanying enhanced somatic excitability can mediate epileptogenic conditions in mammalian central nervous system. As IA channels are dominantly targeted by dendritic and postsynaptic processings during synaptic plasticity, it is presumable that they may act as cellular linkers between synaptic responses and somatic processings under various excitable conditions. In the present study, we electrophysiologically tested if the downregulation of somatic IA channels was sensitive to synaptic activities in young hippocampal neurons. In primarily cultured hippocampal neurons (DIV 6~9), the peak of IA recorded by a whole-cell patch was significantly reduced by high KCl or exogenous glutamate treatment to enhance synaptic activities. However, the pretreatment of MK801 to block synaptic NMDA receptors abolished the glutamate-induced reduction of the IA peak, indicating the necessity of synaptic activation for the reduction of somatic IA. This was again confirmed by glycine treatment, showing a significant reduction of the somatic IA peak. Additionally, the gating property of IA channels was also sensitive to the activation of synaptic NMDA receptors, showing the hyperpolarizing shift in inactivation kinetics. These results suggest that synaptic LTP possibly potentiates somatic excitability via downregulating IA channels in expression and gating kinetics. The consequential changes of somatic excitability following the activity-dependent modulation of synaptic responses may be a series of processings for neuronal functions to determine outputs in memory mechanisms or pathogenic conditions.